Funding community education in Ireland: Making the case for a needs-based approach - Magrath, Conor Joseph; Fitzsimons, Camilla (JSSE - Journal of Social Science Education, 2019)
Purpose: This report captures the experiences of 56 participating community education organisations across Ireland and aims to uncover trends and issues in funding models. Design/methodology/approach: A mixed-methods research was undertaken in three phases. Phase one involved an online- survey, which asked about primary and secondary sources of funding, ease of administration, access and sustainability. Phase two consisted of one-to-one interviews with self-selected providers and in phase three, we returned to the participants of phase two with targeted questions specifically relating to the pressures to merge with non-independent, state providers of community education. Findings: A disconnect between funders and providers, has been highlighted. Particularly the outcomes based funding model, which prioritises jobs activation over social inclusion. Funding is seen as restrictive, anti-innovative, bureaucratic and non-transparent. Practical implications: A need for sustainable, multi-annual funding has been identified, with providers looking for greater acknowledgement and recognition of the vital role and true value of community education in Irish society.